THE EFFECT OF GUIDED INQUIRY METHOD ON SCIENCE PROCESS SKILLS VIEWED FROM THE LEARNING STYLES - Santi Nurrita; Suroyo Suroyo; Mestika Sekarwinahyu; M. Zainal Arifin (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2023)
This quasi-experimental study aims to determine the effect of the guided inquiry method on science process skills in terms of students' learning styles. The population of this study was all fifth grade students at SDN Leuwiliang 04, Bogor Regency, even semester of the 2021/2022 academic year as many as 68 people. When the research was carried out in June 2022 for 4 face-to-face meetings. The statistical test used is in the form of a 2x2 ANOVA inferential test. The results showed that the F_(count) price was 29.044 the F_table(1:59) price was 4.00 and the sig. = 0.00 0.05, so there are differences in science processing skills between students with introverted and extroverted learning styles. The second hypothesis shows that the F_(count) price is 1.859 the F_table(1:59) price is 4.00 and the sig. = 0.00 0.05, there is a difference in the science processing skills of the group of students who were treated with conventional methods and guided inquiry. In the third hypothesis, it shows that the price of F_(count) is 205.915 the price of F_table(1:59) is 4.00 and the sig. = 0.178 0.05, so there is no significant interaction between learning styles and learning methods on science process skills. There are differences in the learning styles of introvert students using the guided inquiry method towards science process skills and there are differences in the learning styles of extrovert students using the guided inquiry method towards science process skills